The Decision to Invest in Child Quality over Quantity : Household Size and Household Investment in Education in Vietnam - Dang, Hai-Anh H.; Rogers, F. Halsey (Published by Oxford University Press on behalf of the World Bank, 2017)
During Vietnam’s two decades of rapid economic growth, its fertility rate has fallen sharply at the same time that its educational attainment has risen rapidly—macro trends that are consistent with the hypothesis of a quantity-quality tradeoff in child-rearing. We investigate whether the micro-level evidence supports the hypothesis that Vietnamese parents are in fact making a tradeoff between quantity and “quality” of children. We present private tutoring—a widespread education phenomenon in Vietnam—as a new measure of household investment in children’s quality, combining it with traditional measures of household education investments. To assess the quantity-quality tradeoff, we instrument for family size using the commune distance to the nearest family planning center. Our IV estimation results based on data from the Vietnam Household Living Standards Surveys (VHLSSs) and other sources show that rural families do indeed invest less in the education of school-age children who have larger numbers of siblings. This effect holds for several different indicators of educational investment and is robust to different definitions of family size, identification strategies, and model specifications that control for community characteristics as well as the distance to the city center. Finally, our estimation results suggest that private tutoring may be a better measure of quality-oriented household investments in education than traditional measures like enrollment, which are arguably less nuanced and less household-driven.